Market valuation of pension liabilities - Greenwood, Mark (My University, 2011)
This dissertation analyses the market-consistent valuation of liabilities for de¯ned-bene¯t pensions in payment. Models from the actuarial and ¯nan- cial economics literature for valuation of in°ation options embedded in typical liabilities in the South African market are considered. The feasibility of the assumptions underpinning these models is then appraised and it is concluded that, while existing models may produce reasonable market valuations for pen- sion liabilities, these models are unable to capture important aspects of the dynamics of the interest rate and in°ation markets. The market for pension liabilities is incomplete due to background risks such as mortality, credit, reg- ulatory and tax risks. Stochastic mortality models are considered and it is described how an incomplete-market valuation of liabilities using risk-adjusted pricing principles may be produced by extending an investment model to in- clude mortality.